Eleven healthy live births: a result of simultaneous preimplantation genetic testing of α- and β-double thalassemia and aneuploidy screening - Chen, Dongjia; Shen, Xiaoting; Wu, Changsheng; Xu, Yan; Ding, Chenhui; Zhang, Guirong; Xu, Yanwen; Zhou, Canquan (Journal of assisted reproduction and genetics, 2020)
Purpose To evaluate the efficacy of preimplantation genetic testing (PGT) for α- and β-double thalassemia combined with aneuploidy screening using next-generation sequencing (NGS). Methods An NGS-based PGT protocol was performed between 2017 and 2018 for twelve couples, each of which carried both α- and β-thalassemia mutations. Trophectoderm biopsy samples underwent whole-genome amplification using multiple displacement amplification (MDA), followed by NGS for thalassemia detection and aneuploidy screening. A selection of several informative single nucleotide polymorphisms (SNPs) established haplotypes. Aneuploidy screening was performed only on unaffected noncarriers and carriers. Unaffected and euploid embryos were transferred into the uterus through frozen-thawed embryo transfer (FET). Results A total of 280 oocytes were retrieved following 18 ovum pick-up (OPU) cycles, with 182 normally fertilized and 112 cultured to become blastocysts. One hundred and seven (95.5%, 107/112) blastocysts received conclusive PGT results, showing 56 (52.3%, 56/107) were unaffected. Thirty-seven (66.1%, 37/56) of the unaffected were also identified as euploid. One family had no transferable embryos. Unaffected and euploid embryos were then transferred into the uterus of the other 11 couples resulting in 11 healthy live births. The clinical pregnancy rate was 61.1% (11/18) per OPU and 68.8% (11/16) per FET, with no miscarriage reported. Seven families accepted the prenatal diagnosis and received consistent results with the NGS-based PGT. Conclusion This study indicated that NGS could realize the simultaneous PGT of double thalassemia and aneuploidy screening in a reliable and accurate manner. Moreover, it eliminated the need for multiple biopsies, alleviating the potential damages to the pre-implanted blastocysts.